Strategic Role of Efficiency to Cash Management: Evidence from Cash Flow Statement of Selected Manufacturing Companies in Nigeria - alayemi, sunday; Salaudeen, Hussain Adebayo (Finance & Economics Review, 2020)
Purpose: The study aims to examine the strategic role of efficiency to cash management, more specifically as it relates to cash generated from operations of manufacturing companies in Nigeria. Method: Annual cash flow statements of selected manufacturing companies in Nigeria for ten years (2009 -2018) were used to conduct the Pooled Test, Random Test, Fixed Effect, and Hausman Test. Results: The results showed that efficiency has a significant effect on the cash management of manufacturing companies in Nigeria generally coupled with that of the proxies employed (CULC, LTDC, INTC, and EARQ) to measure cash management. Implications: In view of the empirical evidence, the study proffered that cash generated from the operation is very crucial and the most reliable means of generating funds for operation because it is internal; unlike funds generated from investing and financing activities.